Amikacin Liposomal Inhalation Suspension in the Treatment of Mycobacterium abscessus Lung Infection: A French Observational Experience. (11th September 2022) - Chiron, Raphael; Hoefsloot, Wouter; Van Ingen, Jakko; Marchandin, Hélène; Kremer, Laurent; Morisse-Pradier, Hélène; Charriot, Jeremy; Mallet, Jean-Pierre; Herrmann, Jean-Louis; Caimmi, Davide; Moreau, Johan; Dumont, Yann; et al.
Abstract: Background: Mycobacterium abscessus infections remain difficult to manage in both cystic fibrosis (CF) and non-CF patients and reported clinical outcomes are largely unsatisfactory. Clinical trial data are limited and no approved therapies are currently available for the management of M abscessus lung diseases. As an alternative, cohort studies may provide insightful information into the management of M abscessus pulmonary disease. Methods: Based on a retrospective observational cohort study, we investigated the safety and efficacy of amikacin liposome inhaled suspension (ALIS) as an adjunct to a standard antibiotic regimen for M abscessus lung infection in both CF and non-CF patients. We also assessed the association of patient drug compliance with culture conversion and clinical outcomes. Results: Twenty-six patients had long-term follow-up data available. Culture conversion was achieved in 54% (14/26) of the patients with no difference between CF and non-CF patients after an average treatment duration of 10 months. Patient treatment compliance was significantly better in the converter group compared to nonconverters with an odds ratio of 44.78 associated with good compared to poor patient compliance. Overall, 9 patients (35%) experienced an adverse event that led to treatment discontinuation. Conclusions: ALIS appears beneficial in both CF and non-CF populations with M abscessus lung disease. Abstract : A French observational cohort study investigated amikacin liposome inhaled suspension as an adjunct to antibiotic regimen for M abscessus lung infection. Sputum culture conversion was achieved in 54% (14/26) of patients with acceptable safety profile after 6 months of treatment.